Peran Manajemen Sumber Daya Pendidikan Islam dalam Membentuk Karakter Siswa - Syahrida Syahrida; Musyarapah Musyarapah (Indo Publishing, 2026)
This study aims to analyze the role of Islamic educational resource management in shaping student character in educational institutions. Superior student character is a pressing need amidst the challenges of moral degradation and the negative influences of the digital era. Islamic educational resource management encompasses the management of teaching staff, administrative staff, students, and infrastructure integrated with Islamic values. This study employed a qualitative approach with a case study method at an Integrated Islamic Junior High School in Central Kalimantan. Data collection techniques included participant observation, in-depth interviews, and documentation. Data analysis employed the interactive model of Miles, Huberman, and Saldaña. The results indicate that Islamic educational resource management plays a significant role in shaping student character through three main functions: values-based strategic planning, effective resource organization, and continuous evaluation. A novel finding of this study is the integrated model of resource management based on the educator's